2021
DOI: 10.3390/ijerph18062951
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Effect of Preterm Birth on Renal Function: A Meta-Analysis

Abstract: The preterm-born adult population is ever increasing following improved survival rates of premature births. We conducted a meta-analysis to investigate long-term effects of preterm birth on renal function in preterm-born survivors. We searched PubMed and EMBASE to identify studies that compared renal function in preterm-born survivors and full-term-born controls, published until 2 February 2019. A random effects model with standardized mean difference (SMD) was used for meta-analyses. Heterogeneity of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Chronic disease multimorbidity was defined as one individual having records of two or more non-communicable chronic diseases (psychiatric or somatic) during the same or subsequent secondary care episode(s). The diseases constituting multimorbidity were selected based on evidence on commonly occurring diseases among preterm and term born adolescents and young adults [21,24,25,[36][37][38][39][40][41][42][43][44]. Multimorbidity was identified using data on both in-patient and out-patient hospital care (referred to in the Nordic context as specialised healthcare), based on diagnostic codes listed in S1…”
Section: Chronic Disease Multimorbiditymentioning
confidence: 99%
“…Chronic disease multimorbidity was defined as one individual having records of two or more non-communicable chronic diseases (psychiatric or somatic) during the same or subsequent secondary care episode(s). The diseases constituting multimorbidity were selected based on evidence on commonly occurring diseases among preterm and term born adolescents and young adults [21,24,25,[36][37][38][39][40][41][42][43][44]. Multimorbidity was identified using data on both in-patient and out-patient hospital care (referred to in the Nordic context as specialised healthcare), based on diagnostic codes listed in S1…”
Section: Chronic Disease Multimorbiditymentioning
confidence: 99%
“…There are not only cardiovascular abnormalities but also renal consequences of prematurity and early life events. A systematic review of preterm birth effects on kidneys found those born preterm had a lower glomerular filtration rate, lower effective renal plasma flow, and a higher urine albumin to creatinine ratio compared to those born at term [ 63 ]. They also found smaller kidney length and kidney volume in addition to higher blood pressure in those born preterm.…”
Section: Neonatal Risk Factors For Later Development Of Cardiovascula...mentioning
confidence: 99%
“…According to the results of a recent meta-analysis, preterm children and adults presented significantly decreased kidney length and volume, GFR and increased microalbuminuria, whereas serum levels of blood urea nitrogen, creatinine and cystatin C did not present any significant difference between preterm and full-term individuals. This finding indicates that traditional biomarkers may not reflect mild renal impairment as long as the renal function is maintained by the remained nephrons [ 47 ]. In another meta-analysis, children and adults with LBW had approximately 70% greater risk of developing CKD in later life, which was defined as albuminuria, low eGFR or end-stage renal disease (ESRD) [ 48 ].…”
Section: Prematurity and Kidneysmentioning
confidence: 99%
“…Subgroup analyses demonstrated that higher systolic BP was identified from early adolescence until adulthood among those born preterm and that the difference in systolic BP was greater in the extreme and very preterm born individuals compared to term [ 73 ]. In other meta-analyses, where BP was measured by both single-time office and ambulatory BP monitoring, preterm born adults compared to full term presented significantly higher systolic BP (mean difference: 4.2 mmHg), diastolic BP (mean difference: 2.6 mmHg) and 24 h ambulatory systolic BP (difference: 3.1 mmHg) [ 47 , 74 , 75 ]. Moreover, another meta-analysis reported additional differences in both sleeping and awake systolic BP and diastolic BP levels between the groups of preterm and term and significantly higher values of other components of metabolic syndromes, such as fasting glucose, insulin, Homeostasis Model Assessment-Estimated Insulin Resistance Index and total cholesterol levels in the group of preterm [ 75 ].…”
Section: Prematurity and Cardiovascular Diseasementioning
confidence: 99%